Mie Kering Berbahan Baku Ubi Jalar (Formulasi, Proses Produksi, Karakteristik Produk) - Dewi Sarastani (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2011)
The purpose of this research  is to study the processing of  Ipomoea batatas L based dry noodle . Dry noodle is successfully made from corm of the Ipomoea batatas L, without starting from flour. Noodle's production steps are braising of corm, mixing corm with supplement material, braising of noodle dough, making of noodle sheets,  steaming and drying the noodle’s circuits ,  dry noodle's packaging.  The result shows that mie[noodle] from  purple parsnip have organoleptic's score to perceive, color, aroma, and elasticity that equals with  mie from wheat, but has ekstensibility's score inferior than mie from wheat. Chemical contents  of Purple Parsnip’s mie are 11.34% of moisture content, 6.68% of  protein, 0.94% of fat, 5.02% of ash, and 1.1% of fiber.  According to Indonesian National Standart [number 01 3551 2000], the moisture and protein content of Purple Parsnip’s mie meet  to instant mie specification.Keyword : corm, Ipomoea batatas L, mie